Rubber waterproof roll as well as preparation method and application thereof

By using styrene-ethylene/butene-styrene copolymer and other materials, the masterbatch forms a thermoplastic rubber with high elasticity and low permanent deformation, and combining a fluorocarbon film layer and a butyl rubber layer, the solution is solved The existing waterproof coils have accelerated aging and poor processing performance due to stress concentration, achieving good performance and environmental protection characteristics in complex environments.

CN119241978APending Publication Date: 2025-01-03DAYU JIUDING NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411407851.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing waterproof coils have problems such as aging caused by concentrated stress, pulling and curling edges, and have poor processing performance, making it difficult to adapt to complex base layers and low temperature environments.

Method used

The masterbatch for rubber waterproof coils is prepared by using styrene-ethylene/butene-styrene copolymer and styrene-ethylene/propylene-styrene copolymer. The structure and physical crosslinking network are formed by microscopic separation, high elasticity, Low permanent deformation thermoplastic rubber combines fluorocarbon film layer and butyl rubber layer to improve flexibility and weather resistance.

Benefits of technology

It achieves good bending properties and stable performance under high temperature environment at low temperatures of -40℃, avoids aging problems caused by stress concentration, and does not require vulcanization. The scraps can be recycled and reused, green and environmentally friendly, suitable for complex base surfaces and extremes. Construction environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005077170790000091
    Figure BDA0005077170790000091
  • Figure BDA0005077170790000101
    Figure BDA0005077170790000101
Patent Text Reader

Abstract

The invention discloses a rubber waterproof coiled material and a preparation method and application thereof, and the rubber waterproof coiled material is prepared from master batch for the rubber waterproof coiled material. The master batch for the rubber waterproof coiled material is prepared from the following raw materials in parts by weight: 45 to 60 parts of styrene-ethylene / butylene-styrene copolymer, 10 to 15 parts of styrene-ethylene / propylene-styrene copolymer, 25 to 30 parts of thermoplastic polyolefin elastomer, 15 to 20 parts of ethylene-butylene-propylene copolymer, 0.5 to 1 part of antioxidant, 0.5 to 1 part of light stabilizer, 1 to 5 parts of pigment and 2 to 5 parts of rubber wear-resistant agent. The elastic recovery rate of the rubber waterproof coiled material can reach 80% or above, and a low-temperature bending test shows that the rubber waterproof coiled material can be suitable for a low-temperature environment with the temperature being lower than-40 DEG C, can resist the high temperature of 100 DEG C and can resist artificial weathering aging for not less than 2500h. And the construction application of the waterproof coiled material in a complex base plane and an extreme construction environment can be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of building materials, and in particular relates to a rubber waterproof coiled material and a preparation method and application thereof. Background Art

[0002] At present, the construction industry has increasingly higher requirements for waterproofing membranes. Although the current mainstream thermoplastic polyolefin TPO waterproofing membranes have high strength and excellent water resistance, they also have some defects, such as: they are not easy to bend, and the stress concentration on the membrane leads to large shrinkage in the later stage, which makes the waterproof layer of the membrane produce large internal stress, accelerates its aging, and causes phenomena such as pulling off and warping at the lap joints. In applications, the construction technology requirements are high, and the nodes with complex structures have many lap joints, which are difficult to fully bond with the base layer, and are prone to leakage due to poor bonding of the joints. EPDM membranes have excellent high temperature resistance and good elasticity at low temperatures, but poor tear resistance and are difficult to lay on uneven and complex bases and special-shaped surfaces. Due to the need for vulcanization during processing, current waterproof membranes generally have poor welding performance, and the generated scraps are difficult to recycle and reuse. Summary of the invention

[0003] In order to overcome the problems existing in the prior art, one of the purposes of the present invention is to provide a masterbatch for rubber waterproofing membrane.

[0004] A second object of the present invention is to provide a rubber waterproofing membrane.

[0005] A third object of the present invention is to provide a method for preparing a rubber waterproofing membrane.

[0006] A fourth object of the present invention is to provide the masterbatch for the rubber waterproofing membrane and the application of the rubber waterproofing membrane in building construction materials.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is:

[0008] The first aspect of the present invention provides a masterbatch for rubber waterproofing coiled material, comprising the following raw materials in parts by weight: 45 to 60 parts of styrene-ethylene / butylene-styrene copolymer, 10 to 15 parts of styrene-ethylene / propylene-styrene copolymer, 25 to 30 parts of thermoplastic polyolefin elastomer, 15 to 20 parts of ethylene-butylene-propylene copolymer, 0.5 to 1 part of antioxidant, 0.5 to 1 part of light stabilizer, 1 to 5 parts of pigment, and 2 to 5 parts of rubber wear resistance agent.

[0009] The inventor has found through a large amount of research that at room temperature, the polystyrene (PS) hard plastic segment of styrene-ethylene / butylene-styrene copolymer (SEBS) and the ethylene / butylene (EB) elastic block in the middle are thermodynamically incompatible with each other, thereby producing a two-phase structure in a microscopic separation state. The PS hard plastic segment of SEBS forms a phase region, is dispersed in the rubber phase formed by the EB elastic block, and forms a physical cross-linking network with the EB elastic block. The characteristic of this structure is that they are strung together or grafted with resin segments (hard segments) and rubber segments (elastic soft segments) with different chemical compositions at the same time, and the hard segments form physical "cross-linking points", while the soft segments are high elastic segments with larger free rotation ability. The hard segments play the role of restraining macromolecular components and reinforcing effects at room temperature, and have reversibility, that is, the restraining force is lost at high temperature, and it is plastic. When the temperature drops to room temperature, the "cross-linking" is restored, playing a role similar to the cross-linking points of vulcanized rubber, and also producing a reinforcing effect. Due to the structural characteristics of the polymer chain segment and the reversibility of the cross-linking state, it shows physical and mechanical properties such as elasticity and deformation characteristics of vulcanized rubber at room temperature, and can be used to produce products with vulcanized rubber properties; on the other hand, at high temperatures, the PS hard plastic segment will melt and flow plastically, showing the processing characteristics of thermoplastic plastics. Using these characteristics of SEBS, a masterbatch for thermoplastic rubber waterproofing membrane that is weather-resistant and low-temperature-resistant, highly elastic and has low permanent deformation can be prepared.

[0010] Preferably, the styrene-ethylene / butylene-styrene copolymer contains 25-30% by mass of styrene monomer units. The styrene-ethylene / butylene-styrene copolymer (SEBS) contains hydrogenated polybutadiene.

[0011] Preferably, the styrene-ethylene / butylene-styrene copolymer is a linear triblock copolymer.

[0012] Preferably, the degree of hydrogenation of the styrene-ethylene / butylene-styrene copolymer is not less than 97%.

[0013] In the present invention, when the block ratio m(styrene monomer unit, S) / m(butylene monomer unit, B) of the styrene-ethylene / butylene-styrene copolymer increases within a certain range, the strength, hardness, and permanent deformation at break of SEBS increase, and the elongation at break decreases. When the block ratio m(S) / m(B) of SEBS is 25 / 75 to 30 / 70, its comprehensive performance is good. In addition, the degree of hydrogenation of SEBS is closely related to its mechanical properties, and the degree of hydrogenation directly determines the mechanical properties of SEBS after aging. In order to ensure that the prepared waterproof coil has excellent aging resistance, the degree of hydrogenation of SEBS is not less than 97%. When the content of 1,4-polybutadiene structural units in the SEBS molecule is too high, the SEBS material will show polyethylene (PE) crystallization phenomenon at room temperature. Crystallization reduces the volume of the amorphous phase in the polymer, increases the driving force of phase separation, makes the phase separation complete, increases the microscopic physical crosslinking density, increases the tensile strength of the material, but increases the plasticity of the material and increases the permanent deformation of the material at break; when the 1,2-polybutadiene structure content in the SEBS base rubber is too high, although it can inhibit the crystallization of polyethylene after hydrogenation, the material has too much poly-1-butene structure, and its low-temperature glass transition temperature Tg rises significantly, the microscopic phase separation driving force decreases, and the microscopic physical crosslinking density decreases, resulting in a decrease in the elasticity and viscosity of the material, which is specifically manifested in the decrease in the 300% tensile stress and tensile strength at break of the material. When the 1,2-structure content in polybutadiene is 35-45%, the crystallinity and glass transition temperature of the ethylene-butene copolymer segment (ie, the EB segment) can achieve a good balance, and the low temperature resistance of the material can reach below -40°C, and the comprehensive mechanical properties are good. Therefore, in the present invention, the styrene-ethylene / butylene-styrene copolymer is preferably at least one of the products of Japan Asahi Kasei H-series with the brand name H1031 and Japan Asahi Kasei H-series with the brand name H1041.

[0014] Preferably, the styrene-ethylene / propylene-styrene copolymer contains less than 20% by mass of styrene monomer units. The styrene-ethylene / propylene-styrene copolymer (SEPS) contains hydrogenated polyisoprene and is a linear triblock copolymer.

[0015] Preferably, the melt flow rate of the styrene-ethylene / propylene-styrene copolymer measured at 230° C. and 2.16 kg is less than 5 g / 10 min.

[0016] Unlike SEBS, styrene-ethylene / propylene-styrene copolymer (SEPS) has a shorter series of methyl units and therefore does not crystallize. There is no crystallization in the EP rubber segment, so SEPS is softer than partially crystallized SEBS, and the elasticity and hysteresis behavior of SEPS are better than the corresponding SEBS; when it is introduced into SEBS as a plasticizer for the rubber segment, the flexibility of the resulting thermoplastic elastomer is further improved, and the oil precipitation problem of traditional oil-filled SEBS can also be solved. Preferably, the styrene-ethylene / propylene-styrene copolymer is at least one of the products of Japan Kuraray SEPTON2000 series with the brand number 2004F and Japan Kuraray SEPTON2000 series with the brand number 2005.

[0017] Preferably, the ethylene-butene-propylene copolymer contains 15-20% by mass of ethylene monomer units and 3-5% by mass of butene monomer units. The butene monomer in the ethylene-butene-propylene copolymer is 1-butene, which is a ternary random copolymer.

[0018] Preferably, in the thermoplastic polyolefin elastomer, the total mass percentage of α-olefin monomer units is 10-20%. The propylene component in the thermoplastic polyolefin elastomer has isotactic stereochemical properties and is evenly distributed between or within molecules.

[0019] In the present invention, the mass percentage of propylene monomer units in the thermoplastic polyolefin elastomer exceeds 80%, the amorphous ethylene propylene segments (EP) are connected together by uniformly dispersed isotactic polypropylene crystals, and are uniformly distributed between or within molecules. The crystallinity of the isotactic polypropylene segments is 5% to 15%. The elastomer of this structure has a high amorphous region content and has good flexibility and low-temperature bending resistance. Preferably, the thermoplastic polyolefin elastomer is at least one of the products of ExxonMobil Vistamaxx series with the brand number 6102 and the products of ExxonMobil Vistamaxx series with the brand number 6202.

[0020] Preferably, the thermoplastic polyolefin elastomer contains isotactic polypropylene segments with a crystallinity of 5 to 15%.

[0021] Preferably, the rubber wear resistant agent is a silicone polymer.

[0022] Preferably, the mass percentage of silicon in the silicone polymer is greater than 70%.

[0023] Preferably, the particle size of silicon dioxide in the silicone polymer is less than 5 μm.

[0024] In the present invention, the rubber wear-resistant agent is a silicone plastic powder without an organic carrier. It overcomes the weakness of traditional silicone oil as a plastic additive; it has the characteristics of high silicone content, large molecular weight, no precipitation on the surface, and no slipping during extrusion in the screw. It can be applied to thermoplastic rubber to improve processing performance and surface wear resistance. The silica particle size in silicone is less than 5μm, and it can be evenly dispersed on the surface of the film material after molding, and can form many fine and hard protrusions on the surface of the film material, thereby reducing the contact area between the surfaces of the film material, achieving the purpose of reducing the friction coefficient of the surface of the film material, and enhancing its wear resistance. At the same time, due to the presence of these protrusions, it is easy for external air to enter between the film materials, avoiding the formation of a vacuum between the two layers of film materials bonded together, thereby playing an anti-sticking and wear-resistant role. Preferably, the rubber wear-resistant agent is Chengdu Silike silicone powder LYSI-100A.

[0025] Preferably, the antioxidant is selected from at least one of hindered phenol antioxidants, phosphite antioxidants, and thioester antioxidants; further preferably, the antioxidant is selected from at least one of BASF antioxidant 168 and BASF antioxidant 1076.

[0026] Preferably, the light stabilizer is selected from at least one of benzophenone ultraviolet light absorbers, benzotriazole ultraviolet light absorbers, and hindered amine light stabilizers. Further preferably, the light stabilizer is selected from at least one of BASF's light stabilizer chimassorb622, BASF's light stabilizer chimassorb944, and BASF's light stabilizer chimassorb2020.

[0027] Preferably, the pigment is selected from at least one of titanium dioxide, carbon black and benzimidazolone pigments.

[0028] Preferably, the average particle size of the masterbatch is 2.5 to 3 mm.

[0029] Preferably, the method for preparing the masterbatch for rubber waterproofing coiled material comprises the following steps:

[0030] The raw materials for preparing the rubber waterproof coiled material are mixed and then granulated to obtain the masterbatch for the rubber waterproof coiled material.

[0031] Preferably, the mixing step comprises:

[0032] Step (a): mixing styrene-ethylene / butylene-styrene copolymer, styrene-ethylene / propylene-styrene copolymer and rubber wear-resistant agent;

[0033] Step (b): the mixture is then mixed with the remaining raw materials and granulated using a twin-screw extruder.

[0034] Preferably, the mixing temperature in step (a) is 50-60°C.

[0035] Preferably, the mixing step in step (a) is performed by stirring and mixing at a stirring rate of 150 to 250 r / min.

[0036] Preferably, the mixing time in step (a) is 5 to 10 minutes.

[0037] Preferably, the mixing temperature in step (b) is 70-80°C.

[0038] Preferably, the mixing step in step (b) is performed by stirring and mixing at a stirring rate of 300 to 400 r / min.

[0039] Preferably, the mixing time in step (b) is 20 to 30 minutes.

[0040] Preferably, in step (b), the die temperature of the twin-screw extruder is 180-200°C.

[0041] Preferably, in step (b), the extrusion rate of the twin-screw extruder is 3 to 4 m / min.

[0042] The second aspect of the present invention provides a rubber waterproofing membrane, comprising an elastic layer; the elastic layer is made of the masterbatch for the rubber waterproofing membrane described in the first aspect of the present invention.

[0043] Preferably, the rubber waterproof coiled material comprises a fluorocarbon film layer, an adhesive layer and an elastic layer which are stacked in sequence.

[0044] Preferably, the elastic layer has a thickness of 1.2-1.5 mm.

[0045] Preferably, the fluorocarbon film layer has a thickness of 0.02-0.05 mm.

[0046] Preferably, the thickness of the adhesive layer is 0.15-0.25 mm.

[0047] Preferably, the fluorocarbon film layer is selected from at least one of polytetrafluoroethylene resin film, polyvinylidene fluoride resin film, polychlorotrifluoroethylene / vinyl ether resin film and polyvinyl fluoride resin film.

[0048] In the present invention, the fluorocarbon film layer is extruded from a copolymer of fluorine and fluorocarbon molecules, and is a copolymer containing fluorine or fluorocarbon, which has greater chemical bonding force and structural stability than other polymers. Its chemical structure is bonded by fluorine-carbon bonds, and this structure with short bond properties forms the most stable and firm bond with hydrogen ions. Therefore, the fluorocarbon polymer has excellent physical and chemical properties, not only has strong weather resistance and corrosion resistance, but also has high fading resistance and UV resistance in extremely harsh and adverse environments. The waterproof roll formed by compounding it on the elastic layer in the present invention has greatly improved performance in exposed applications.

[0049] Preferably, the adhesive layer is a butyl adhesive layer.

[0050] Preferably, the butyl rubber layer contains butyl rubber and polyisobutylene.

[0051] Preferably, the mass percentage of butyl rubber in the butyl rubber layer is not less than 30%.

[0052] Preferably, the mass percentage of polyisobutylene in the butyl rubber layer is not less than 20%.

[0053] In the present invention, the butyl rubber layer is a butyl pressure-sensitive adhesive with butyl rubber and polyisobutylene as the main resin materials. Since its chemical structure is similar to that of butyl rubber and has good compatibility, it is used as an intermediate bonding layer between the fluorocarbon film layer and the resilience modified rubber layer. It has excellent bonding performance and is easy to achieve full adhesion of the two-layer structure. In addition, the saturation degree of butyl rubber is extremely high, and it is very outstanding in heat and weather resistance.

[0054] The third aspect of the present invention provides a method for preparing the rubber waterproofing membrane according to the first aspect of the present invention, comprising the following steps:

[0055] The rubber waterproof coiled material is extruded and molded using master batches, and then rolled to obtain the rubber waterproof coiled material.

[0056] Preferably, the rolling step uses a three-roll calender.

[0057] Preferably, the three-roll calender is cooled by refrigerated circulating water.

[0058] Preferably, the water temperature of the refrigeration circulating water is 0-8°C, and the water cooling heat exchange effect is better at this temperature.

[0059] Preferably, the extrusion molding step is performed by using a screw extruder.

[0060] Preferably, the preparation method further comprises step a, which is located after the rolling step, and step a is: applying glue on a glue coating machine to form an adhesive layer, and then compounding it with the fluorocarbon film layer.

[0061] The third aspect of the present invention provides the use of the rubber waterproof membrane described in the first aspect of the present invention in building construction materials.

[0062] The beneficial effects of the present invention are as follows: compared with traditional thermoplastic polyolefins, the masterbatch for rubber waterproofing membranes in the present invention does not contain unsaturated chemical bonds and small molecule plasticizers, maintains excellent mechanical properties and weather resistance and corrosion resistance after exposure tests, does not require vulcanization, does not contain cross-linked chemical bonds, and scraps can be recycled without damaging their physical and chemical properties and processing performance. It is green and environmentally friendly and has better flexibility and resistance to low-temperature brittleness.

[0063] The rubber waterproofing membrane in the present invention is soft, has an elastic recovery rate of more than 80%, has good bending properties at a low temperature of -40°C, and can be used in a low temperature environment with a temperature less than -40°C. It has good high temperature resistance and can be used normally in a high temperature environment of 100°C. It is resistant to artificial weathering for not less than 2500h, and can meet the construction application of waterproofing membranes on complex base surfaces and extreme construction environments. In addition, the waterproofing membrane in the present invention has good adhesion and can be used together with a variety of substrates for construction, adapting to the construction of various complex scene nodes. DETAILED DESCRIPTION

[0064] The specific implementation of the present invention is further described in detail below in conjunction with examples, but the implementation and protection of the present invention are not limited thereto. It should be noted that if there are processes that are not particularly described in detail below, they can be implemented or understood by those skilled in the art with reference to the prior art. The reagents or instruments used that do not indicate the manufacturer are all conventional products that can be purchased commercially.

[0065] The raw material information used in the examples and comparative examples of the present invention is as follows:

[0066] The styrene-ethylene / butylene-styrene copolymer is H1031 of the H-series series of Asahi Kasei of Japan;

[0067] The styrene-ethylene / propylene-styrene copolymer is 2004F of SEPTON2000 series of Japan Kuraray;

[0068] The thermoplastic polyolefin elastomer is 6102 of ExxonMobil Vistamaxx series;

[0069] The ethylene-butene-propylene copolymer is PP9302 from Yanshan Petrochemical;

[0070] The antioxidant was BASF antioxidant 168;

[0071] The light stabilizer is BASF's light stabilizer chimassorb622;

[0072] The pigment is titanium dioxide;

[0073] The rubber wear-resistant agent is Chengdu Silike silicone powder LYSI-100A.

[0074] Example 1

[0075] This example provides a rubber waterproof roll material with a single-layer structure, which is made of the raw materials in parts by weight listed in Table 1.

[0076] Table 1 Preparation raw material formula of rubber waterproofing membrane in Example 1

[0077] raw material Weight Styrene-ethylene / butylene-styrene copolymer 45 Styrene-ethylene / propylene-styrene copolymer 10 Thermoplastic Polyolefin Elastomer 25 Ethylene-butene-propylene copolymer 15 Antioxidants 0.5 Light Stabilizer 0.5 pigment 1 Rubber wear resistant agent 3

[0078] The rubber waterproofing membrane in this example is prepared by a preparation method comprising the following steps, specifically:

[0079] (1) Put the formulated amount of styrene-ethylene / butylene-styrene copolymer, styrene-ethylene / propylene-styrene copolymer and rubber wear-resistant agent into a mixer, heat it to 50° C., rotate at 150 r / min, and stir for 5 minutes;

[0080] (2) adding the formulated amount of thermoplastic polyolefin elastomer, ethylene-butene-propylene copolymer, antioxidant, light stabilizer and pigment into the mixer of step (1) in sequence, heating to 70° C., rotating at 300 r / min, and stirring for 20 min;

[0081] (3) The mixed material uniformly mixed in step (2) is put into a co-rotating twin-screw extruder with a length-to-diameter ratio of 52 for granulation, and the temperatures from the screw feed port to the die port are set to 180° C., 180° C., 190° C., 190° C., 200° C., and 200° C., respectively, to obtain a masterbatch for rubber waterproof membrane.

[0082] (4) The masterbatch for rubber waterproofing coiled material prepared in step (3) is put into a single screw extruder with an aspect ratio of 30 and a compression ratio of 3, and then a single-layer waterproofing coiled material with a thickness of 1.2 mm is prepared through a T-type flat die and a three-roll calender, which is the rubber waterproofing coiled material in this example. The temperature from the conveying zone to the melting zone of the extruder is set to 80°C, 150°C, 180°C, 180°C, 200°C, and 200°C, and the temperatures of the upper, middle, and lower rollers of the three-roll calender with ice water circulating heat exchange on the lower roller are set to 50°C, 40°C, and 5°C, respectively.

[0083] Example 2

[0084] This example provides a rubber waterproof roll material with a single-layer structure, which is made of the raw materials prepared in parts by weight as shown in Table 2.

[0085] Table 2 Preparation raw material formula of rubber waterproofing membrane in Example 2

[0086] raw material Weight Styrene-ethylene / butylene-styrene copolymer 40 Styrene-ethylene / propylene-styrene copolymer 5 Thermoplastic Polyolefin Elastomer 25 Ethylene-butene-propylene copolymer 25 Antioxidants 0.5 Light Stabilizer 0.5 pigment 1 Rubber wear resistant agent 3

[0087] The rubber waterproofing membrane in this example was prepared by referring to the preparation method described in Example 1.

[0088] Example 3

[0089] The rubber waterproofing membrane in this example is a three-layer structure, which is a fluorocarbon film layer, a butyl rubber layer and an elastic layer stacked in sequence. The elastic layer is a single-layer waterproofing membrane with a thickness of 1.2 mm prepared in Example 1.

[0090] The rubber waterproofing membrane in this example is prepared by a preparation method comprising the following steps:

[0091] First, the single-layer waterproof membrane with a thickness of 1.2 mm prepared in Example 1 is conveyed to a glue coating machine for coating with butyl pressure-sensitive adhesive to form a butyl adhesive layer on the surface of the elastic layer (the butyl adhesive layer is a butyl pressure-sensitive adhesive with butyl rubber and polyisobutylene as the main resin materials, purchased from Nenghui New Materials Technology Co., Ltd., model E8616 butyl adhesive), the thickness of the butyl adhesive layer is 0.25 mm, and the gluing temperature is 130°C. After further compounding with a fluorocarbon film layer DJ-C02 with a thickness of 0.05 mm (purchased from Shijiazhuang Dajia New Materials Technology Co., Ltd., model: fluorocarbon film DJ-C02) through a traction roller, a three-layer rubber waterproof membrane with a thickness of 1.5 mm is obtained.

[0092] Example 4

[0093] The rubber waterproofing membrane in this example is prepared by using the masterbatch for rubber waterproofing membrane prepared in Example 1 according to the preparation steps described in step (3) of Example 1 to form a single-layer waterproofing membrane with a thickness of 1.5 mm.

[0094] Comparative Example 1

[0095] This example provides a waterproof roll material with a single-layer structure, which is made of the raw materials prepared in parts by weight as shown in Table 3. The waterproof roll material in this example is a traditional TPO polyolefin waterproof roll material.

[0096] Table 3 Preparation raw material formula of waterproof membrane in comparative example 1

[0097] raw material Weight Styrene-ethylene / butylene-styrene copolymer 0 Styrene-ethylene / propylene-styrene copolymer 0 Thermoplastic Polyolefin Elastomer 40 Ethylene-butene-propylene copolymer 58 Antioxidants 0.5 Light Stabilizer 0.5 pigment 1 Rubber wear resistant agent 0

[0098] The waterproof roll material in this example is prepared by a preparation method comprising the following steps:

[0099] (1) The raw materials were put into a mixer in sequence according to the formula ratio in Table 3 for premixing, the mixing temperature was 70°C, the speed was 300 r / min, and the stirring was carried out for 20 min;

[0100] (2) The mixed material obtained in step (1) is put into a single screw extruder with a length-to-diameter ratio of 30 and a compression ratio of 3, and then a single-layer waterproof membrane with a thickness of 1.2 mm is prepared through a T-type flat die and a three-roll calender. The temperature from the conveying zone to the melting zone of the extruder is set to 80°C, 150°C, 180°C, 180°C, 200°C, and 200°C, and the temperature of the three-roll calender is set to: 60°C.

[0101] Performance Testing

[0102] The single-layer waterproof membranes prepared in Examples 1 to 2 and Comparative Example 1 were respectively taken, and their Shore A hardness (1 second reading) was tested according to the test method described in GB / T 2411-2008 "Determination of indentation hardness (Shore hardness) of plastics and hard rubber using a hardness tester", and their basic physical properties, low-temperature bendability and impermeability were tested according to the test method described in GB 27789-2011 "Thermoplastic polyolefin (TPO) waterproof membrane". According to the test method described in GB / T 23457-2017 "Pre-laid waterproof membrane", its elastic recovery rate and dimensional change rate were tested. The specific test results are shown in Table 4 below.

[0103] Table 4 Performance test results of single-layer waterproof membranes prepared in Examples 1 to 2 and Comparative Example 1

[0104]

[0105] As shown in Table 4, the rubber waterproofing coiled materials in Examples 1 to 2 of the present invention can meet the basic requirements of waterproofing, bend without cracks at a low temperature of -40°C, have a dimensional change rate of less than 1%, a welding strength of ≥6.5MPa, an elongation at break of ≥690%, and an elastic recovery rate of ≥80%. Compared with Comparative Example 1, the masterbatch components of the rubber waterproofing coiled materials prepared in Examples 1 to 2 of the present invention use styrene-ethylene / butylene-styrene copolymer (SEBS) and styrene-ethylene / propylene-styrene copolymer (SEPS), both of which have a greater effect on the flexibility and elasticity of the coiled materials, and there are more semi-crystalline or non-crystalline regions in their molecules, so they have better low-temperature bending, elongation at break and dimensional change rate. At the same time, non-vulcanized rubber has a relatively low melting temperature requirement in the welding process, so it is extremely efficient during construction welding. The molecules of SEBS and SEPS can be better entangled with each other on the welding surface, the welding strength is higher than TPO, and the waterproof performance of the seam is better. However, the higher the SEBS and SEPS content, the better. Excessive addition will lead to low hardness of the coil, insufficient strength, and reduced construction performance.

[0106] The rubber waterproof membranes prepared in Example 3 and Example 4 and the commercially available 1.5 mm thick TPO waterproof membranes were tested for low-temperature flexure and impermeability according to the test method described in GB / T328.15-2007 "Test methods for building waterproof membranes Part 15: Low-temperature flexure of polymer waterproof membranes", and their 2500 h artificial climate accelerated aging performance was tested according to the test method described in GB / T 18244-2022 "Aging test methods for building waterproof materials". The heat resistance was tested according to the test method described in GB / T 23457-2017 "Pre-laid waterproof membranes", and the heat aging performance was tested according to the test method described in GB 27789-2011 "Thermoplastic polyolefin (TPO) waterproof membranes". The specific test results are shown in Table 5 below.

[0107] Table 5 Performance test results of Examples 3 to 4 and commercially available waterproof membranes

[0108]

[0109] As shown in Table 5, the rubber waterproofing membranes in Examples 3 to 4 of the present invention have no abnormal appearance after 2500 hours of accelerated aging under standard xenon lamp aging conditions, while the commercially available TPO membranes have a powdering phenomenon. Compared with Example 4, Example 3 has a butyl rubber layer and a fluorocarbon film layer on the surface of the waterproofing membrane in Example 1, and its weather resistance is more outstanding. The physical properties of the membrane after aging remain above 90%. At the same time, the good resilience and dimensional stability make the waterproofing membranes of Examples 3 to 4 have good deformation recovery ability and stress dispersion after being stretched or squeezed by stress during application, avoiding accelerated aging due to stress concentration in the later stage of construction, or defects such as the waterproof layer being torn, the lap seam being pulled off and the edge warping.

[0110] In summary, the masterbatch for rubber waterproofing coiled materials modified by blending of the present invention has better flexibility and low-temperature brittleness resistance than traditional thermoplastic polyolefins. The waterproofing coiled materials made with the rubber masterbatch are soft, have good conformability to the base layer, and are suitable for construction of various complex scene nodes. Good resilience enables the rubber waterproofing coiled materials to have good deformation recovery ability and stress dispersion after being stretched or extruded by stress during application. Avoid accelerated aging due to stress concentration in the later stage of construction, or defects such as the waterproof layer being torn, the lap seam being pulled off and warping. Moreover, the masterbatch components for rubber waterproofing coiled materials do not contain unsaturated chemical bonds and small molecule plasticizers, and maintain excellent mechanical properties and weather resistance and corrosion resistance after exposure tests. In addition, the rubber waterproofing coiled materials prepared by the masterbatch for rubber waterproofing coiled materials do not need to be vulcanized, do not contain cross-linked chemical bonds, and the scraps can be recycled and reused without damaging their physical properties and processing properties, which is green and environmentally friendly. The elastic recovery rate of the rubber waterproofing membrane in the present invention can reach more than 80%. The low-temperature bending test shows that it can be used in a low-temperature environment of less than -40°C, can withstand a high temperature of 100°C, and can withstand artificial weathering for not less than 2500h. It can meet the construction application of waterproofing membranes on complex base surfaces and extreme construction environments.

[0111] The rubber waterproofing coiled material in the present invention has good tensile strength, high elongation and low permanent deformation due to the introduction of modified rubber. Its excellent flexibility significantly improves the processing efficiency of the inner and outer corners and special nodes in construction applications, and it fits tightly to the base surface. At the same time, the characteristic of low permanent deformation avoids the accelerated aging and warping and shedding of tensile or extrusion deformation caused by stress concentration in the later stage of construction. Different from EPDM and vulcanized rubber, the rubber of the rubber waterproofing coiled material in the present invention is a saturated chemical bond molecule, does not contain a cross-linking agent and a small molecule plasticizer, has low-temperature flexibility and high temperature resistance. In addition, it not only performs well in welding performance, but also has high compatibility with butyl rubber, and has a good full adhesion effect when used in conjunction with butyl rubber, truly achieving skin-like waterproofing with molecular-level contact.

[0112] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

Claims

1. A masterbatch for rubber waterproofing coiled material, characterized in that: The invention comprises the following raw materials in parts by weight: 45-60 parts of styrene-ethylene / butylene-styrene copolymer, 10-15 parts of styrene-ethylene / propylene-styrene copolymer, 25-30 parts of thermoplastic polyolefin elastomer, 15-20 parts of ethylene-butylene-propylene copolymer, 0.5-1 part of antioxidant, 0.5-1 part of light stabilizer, 1-5 parts of pigment and 2-5 parts of rubber wear-resistant agent.

2. The masterbatch for rubber waterproofing coiled material according to claim 1, characterized in that: The styrene-ethylene / butylene-styrene copolymer contains 25-30% by mass of styrene monomer units; And / or, the styrene-ethylene / propylene-styrene copolymer contains less than 20% by mass of styrene monomer units; and / or, the melt flow rate of the styrene-ethylene / propylene-styrene copolymer measured at 230° C. and 2.16 kg is less than 5 g / 10 min; And / or, the ethylene-butene-propylene copolymer contains 15-20% by mass of ethylene monomer units and 3-5% by mass of butene monomer units.

3. The masterbatch for rubber waterproofing coiled material according to claim 1, characterized in that: In the thermoplastic polyolefin elastomer, The mass percentage of α-olefin monomer units is 10 to 20%; And / or, the thermoplastic polyolefin elastomer contains isotactic polypropylene segments with a crystallinity of 5 to 15%.

4. The masterbatch for rubber waterproofing coiled material according to claim 1, characterized in that: The rubber wear-resistant agent is a silicone polymer. Preferably, the mass percentage of silicon in the silicone polymer is greater than 70%; preferably, the particle size of silicon dioxide in the silicone polymer is less than 5 μm.

5. The masterbatch for rubber waterproofing membrane according to any one of claims 1 to 4, characterized in that: The antioxidant is selected from at least one of hindered phenol antioxidants, phosphite antioxidants, and thioester antioxidants; And / or, the light stabilizer is selected from at least one of benzophenone ultraviolet light absorbers, benzotriazole ultraviolet light absorbers, and hindered amine light stabilizers; And / or, the pigment is at least one selected from titanium dioxide, carbon black, and benzimidazolone pigments.

6. A rubber waterproofing coiled material, characterized in that: It comprises an elastic layer; the elastic layer is made of the masterbatch for rubber waterproofing membrane according to any one of claims 1 to 5.

7. The rubber waterproofing coiled material according to claim 6, characterized in that: The rubber waterproof coiled material comprises a fluorocarbon film layer, an adhesive layer and an elastic layer which are stacked in sequence.

8. The rubber waterproofing coiled material according to claim 7, characterized in that: The thickness of the elastic layer is 1.2 to 1.5 mm; And / or, the thickness of the fluorocarbon film layer is 0.02 to 0.05 mm; And / or, the thickness of the adhesive layer is 0.15 to 0.25 mm; And / or, the fluorocarbon film layer is selected from at least one of polytetrafluoroethylene resin film, polyvinylidene fluoride resin film, polychlorotrifluoroethylene / vinyl ether resin film, and polyvinyl fluoride resin film; And / or, the adhesive layer is a butyl adhesive layer.

9. The method for preparing the rubber waterproofing coiled material according to any one of claims 6 to 8, characterized in that: The following steps are involved: The rubber waterproofing coiled material is extruded and molded using master batches, and then rolled to obtain the rubber waterproofing coiled material.

10. Use of the masterbatch for rubber waterproofing membrane according to any one of claims 1 to 5 and / or the rubber waterproofing membrane according to any one of claims 6 to 8 in building construction materials.